2012
DOI: 10.1097/nxn.0b013e31825108d1
|View full text |Cite
|
Sign up to set email alerts
|

Using Podcasts to Help Students Apply Health Informatics Concepts

Abstract: Despite requirements for robust health informatics education, a multitude of educators and policy analysts report that programs are not adequately preparing nurses to handle the bevy of technologies that will be a part of their practice. A series of 14 "Podcasted" exemplars were developed to help graduate online students visualize the application of health informatics concepts in real-world settings and to determine the impact of podcasting on student cognition, engagement, and satisfaction. Although no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Other study results showed that nursing students positively apprised the use of podcasts to promote their knowledge and confidence about delirium awareness, and 96.32% of nursing students deemed that the podcast met their learning needs about delirium ( 44 ). Two studies also used podcasting to deliver palliative care and health information concepts ( 43 , 45 ). Demonstrate that nursing philosophy knowledge can be released to students through broadcasts not limited to lectures.…”
Section: Resultsmentioning
confidence: 99%
“…Other study results showed that nursing students positively apprised the use of podcasts to promote their knowledge and confidence about delirium awareness, and 96.32% of nursing students deemed that the podcast met their learning needs about delirium ( 44 ). Two studies also used podcasting to deliver palliative care and health information concepts ( 43 , 45 ). Demonstrate that nursing philosophy knowledge can be released to students through broadcasts not limited to lectures.…”
Section: Resultsmentioning
confidence: 99%
“…19 Lyles et al observed that 91.2 per cent of students regularly listened to lecture podcasts and questionnaire survey suggested that the audio podcast was a useful tool for enhancing teaching and learning. 5 In the same study, testimonials provided by three students revealed that podcasts helped them to prepare master notes.…”
Section: Discussionmentioning
confidence: 99%